SAS (SYNTHETIC STRUTURAL ANALYTIC) METHOD IN IMPROVING STUDENT'S READING SKILLS: indonesia - Muhtarom; Eri Purwanti; M. Yusuf Efendi (STIT Pringsewu, 2021)
Abstract The problem in this study is that there are still students who have not been able to read, there are still students who still have difficulty spelling the reading, and there are still low reading skills in students. This study aims to determine the application of the SAS (Synthetic Analytical Structural) method to improve reading skills of grade II students of SDN 1 Wonosari. This type of research is a qualitative method. The research population was class II homeroom teachers, class II students, and principals. The sample of class II students was 13 students. Data collection techniques using interview techniques, observation, documentation. Based on the results of the study, the application of the SAS (Synthetic Analytical Structural) method can improve reading skills of grade II SDN 1 Wonosari students, this can be seen from the progress of students who were not able to read as much as 50% to 70%. Students who had difficulty spelling a reading from 40% to 60%. Based on this, the application of the SAS (Synthetic Analytical Structural) method is very helpful in improving the reading skills of grade II students of SDN 1 Wonosari. Keywords: SAS method, reading skills